Study some of Structural and Optical Properties for Cd1-xFexO Thin Films Prepared by Chemical Bath Deposition (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
CdO thin Films Pure and doping by Fe (2,4,6)% was prepared by Chemical bath deposition (CBD) technique on glass substrates.Thin Films prepared was heated at(300)ᵒC  for 1 h in air. Structural and Optical properties of thin Films had been investigated, (XRD) results Showed that all thin Films have a polycrystalline Structural (FCC) and the higher crystal plane (111), Optical properties results showed that the transmittance of thin Films was decreased with increasing the doping . optical band gab was 2.62 eV at X =0, and 1.89 eV at X= 6%. The results also Showed that the Absorbance of thin Films increase with increasing the doping with high Absorption coefficient in the visible region of electromagnetic spectral